Genome Sequence of Campylobacter jejuni strain 327, a strain isolated from a turkey slaughterhouse. Issue 2 (March 2011) - Takamiya, Monica; Ozen, Asli; Rasmussen, Morten; Alter, Thomas; Gilbert, Tom; Ussery, Dave; Knøchel, Susanne
Abstract Campylobacter is one of the leading causes of food-borne gastroenteritis and has a high prevalence in poultry.Campylobacter jejuni subsp. jejuni 327 is a subspecies of the genusCampylobacter of the familyCampylobacteraceae in the phylumProteobacteria . The microaerophilic, spiral shaped, catalase positive bacterium obtains energy from the metabolism of amino acids and Krebs cycle intermediates. Strain 327 was isolated from a turkey slaughter production line and is considered environmentally sensitive to food processing (cold, heat, drying) and storage conditions. The 327 whole genome shotgun sequence of 1, 618, 613 bp long consists of 1, 740 protein-coding genes, 46 tRNA genes and 3 rRNA operons. A protein based BLAST analysis places the turkey isolate 327 close to the human clinical strain 81116 (NCTC 11828).